AIR POLLUTION AND NOISELABORATORY - ABDUL HAMID , NOR HAZREN (2024)
Air pollution and noise laboratory book presents the hands-on activities that can be performed by students of Bachelor of Civil Engineering Technology (Environment), UTHM which relates to the fundamentals of air pollution and noise control. This book is a student’s guideline for performing experimental works on instruments and devices in controlling air and noise pollution. In chapter 1, the pulsed jet bag filter system has been custom-designed to introduce the students of Civil Engineering Technology to dust pollution control using a fabric filter. Next, in chapter 2, students will determine the cyclone collection efficiency and compare the efficiency of the larger cyclone to the smaller one. Students may also compare the efficiency of a single cyclone operation and a double cyclone operation. In chapter 3, students will demonstrate the spray chamber operations using five different spraying nozzles and study the effect of droplet sizes on separation efficiency. In chapter 4, student will demonstrate venturi scrubber operations by varying several parameters such as liquid to gas (L/G) ratio to estimate its effect on separation efficiency and verify the theoretical relationship between total pressure drop and air inlet velocity. Chapter 5 demonstrates that E-SAMPLER is a type of nephelometer which automatically measures and records real-time airborne of PM10, PM2.5, or TSP particulate concentration levels using the principle of forward laser light scatter. In Chapter 6, student need to determine the air velocity and detect changes in some physical property of the fluid using anemometers or the effect of the fluid on a mechanical device inserted into the flow. Finally, chapter 7 present the measurement of noise engineering, quality control, health prevention and various environmental noise, including noise measurement in such various places around factories, offices, transporting routes, workshops, road and residential.